SALT TASTE THRESHOLD AS A DETECTION OF SALT INTAKE IN HYPERTENSIVE INDIVIDUALS - Afifah Nurma Sari; Farapti Farapti; Norfezah Md Nor (Jurnal Berkala Epidemiologi, 2022)
Background: High sodium consumption is one of the risk factors for hypertension. Excess salt intake may be affected by an individual’s ability to detected taste. However, decreased salt sensitivity can increase consumption of salty foods. Purpose: This review aims to analyze the salt taste threshold and its relation to salt intake among hypertensive and normotensive individuals. Methods: The review was conducted using five electronic databases and fourteen articles reporting on salt taste threshold, salt intake, and blood pressure. Open access articles, original research, published over the past ten years, and subject’s age over eighteen years both healthy and with specific clinical conditions, and have blood pressure data were identified and included in the study. Results: There were fourteen studies that measured salt taste threshold through detection threshold and/ or recognition threshold. Ten studies reported salt consumption through Na-FFQ, SQ-FFQ, 24-hour food recall, discretionary salt, adding salt questionnaire, salt use behavior questionnaire, salt preference questionnaire, and sodium excretion. Most studies showed that high salt consumption is higher in the group with high salt taste threshold and high salt taste threshold tends to be more in hypertensive group. The result also showed a significant correlation between salt consumption both through self-reported questionnaire and 24-hour urinary sodium excretion. Conclusion: Although the correlation between salt taste threshold, salt intake, and hypertension can be found a matching method with adequate statistical power is needed to get more accurate results.